(untitled) - Food & Agriculture Organization of the United Nations (FAO) (Rome, 1995)
This publication is a compilation of aquaculture production statistics for fish, crustaceans, molluscs and other aquatic animal, residues and plants. The following combinations of production statistics are presented: by species and by country; by country and by species; by species and by environment.Values of production expressed in term of USD.
Keywords: Aquaculture,Fisheries